Pelaksanaan Pemeliharaan Rutin Belt Conveyer untuk Meminimalkan Downtime pada UBP PLTU Jeranjang - Anggara, Lalu surya; Sultan; Budiman, Djul Fikri (JEITECH (JOURNAL OF ELECTRICAL ENGINEERING, INFORMATION TECHNOLOGY, CONTROL ENGINEERING, AND ROBOTIC), 2025)
The Field Work Practice (PKL) at UBP PLTU aimed to understand and analyze routine maintenance of the belt conveyor system to reduce downtime. Methods used included direct observation, interviews, data analysis, and post-maintenance condition evaluation. Before implementing routine maintenance, downtime occurred 5–7 times per month due to belt wear, misalignment, motor overheating, and spillage. After applying preventive and condition-based maintenance strategies, downtime significantly decreased to 1–2 times per month, and corrective maintenance needs were reduced by up to 60%. Routine maintenance also helped stabilize motor temperatures, reduce vibration, and extend uninterrupted operating time. Challenges such as delays in spare part procurement and errors in CMMS usage were addressed through technician training and improved monitoring systems. In conclusion, well-planned routine maintenance effectively improves the efficiency and stability of operations. Recommendations include strengthening human resource capacity, enhancing digital monitoring, proactive spare part management, fostering a preventive work culture, and conducting regular evaluations and audits.